2021
DOI: 10.36401/jipo-20-36
|View full text |Cite
|
Sign up to set email alerts
|

JAK Be Nimble: Reviewing the Development of JAK Inhibitors and JAK Inhibitor Combinations for Special Populations of Patients with Myelofibrosis

Abstract: Myelofibrosis (MF) is a myeloproliferative neoplasm hallmarked by uncontrolled blood counts, constitutional symptoms, extramedullary hematopoiesis, and an increased risk of developing acute myeloid leukemia. Janus kinase (JAK) inhibitors are the most common treatment for MF due to their ability to reduce spleen size and improve disease-related symptoms; however, JAK inhibitors are not suitable for every patient and their impact on MF is limited in several respects. Novel JAK inhibitors and JAK inhibitor combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 89 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…JAK/STAT signaling pathway is an important pathway that regulates the polarization direction of macrophages. JAK (Janus kinase) kinase family plays a crucial role in the immune system and is a series of pathological Mediators of Inflammation therapeutic targets, including autoimmune diseases, COVID-19-related cytokine storms, and blood cancer [119,120]. In an in vitro experiment, it was found that peripheral blood-derived mesenchymal stem cells could secret IL-10 to induce the upregulation of JAK1/STAT3 signaling in macrophages, thereby promoting an increase in the expression of M2-type macrophages and M2-related cytokines [121].…”
Section: Macrophage Polarization and Systemic Lupusmentioning
confidence: 99%
“…JAK/STAT signaling pathway is an important pathway that regulates the polarization direction of macrophages. JAK (Janus kinase) kinase family plays a crucial role in the immune system and is a series of pathological Mediators of Inflammation therapeutic targets, including autoimmune diseases, COVID-19-related cytokine storms, and blood cancer [119,120]. In an in vitro experiment, it was found that peripheral blood-derived mesenchymal stem cells could secret IL-10 to induce the upregulation of JAK1/STAT3 signaling in macrophages, thereby promoting an increase in the expression of M2-type macrophages and M2-related cytokines [121].…”
Section: Macrophage Polarization and Systemic Lupusmentioning
confidence: 99%